Pengenalan Rambu Lalu Lintas Pada Anak Usia Dini Menggunakan Media Pembelajaran Berbasis Augmented Reality Di TK Islam Annur Cilegon - Suherman; Ikna Niswatuzzakiah; Gugun Gunawan (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The level of understanding of early childhood regarding traffic signs is still relatively low. Based on initial observations at TK Islam Annur Cilegon, it was found that 90% of children were unable to recognize the shape and meaning of basic traffic signs. This problem is caused by the use of conventional learning media. As a solution, the Student Creativity Program (PKM) team developed and implemented interactive Augmented Reality (AR)-based learning media that allows children to recognize traffic signs through 3D objects in a real and enjoyable way. The activity was carried out in three stages, namely preparation, socialization implementation, and evaluation, involving 20 children as the activity model. The evaluation results showed a very significant improvement in children's understanding, from an average pre-test score of 4% to 91% in the post-test. This 87% improvement proves that Augmented Reality-based learning media is effective in improving the understanding and learning interest of early childhood toward traffic signs.